1963
DOI: 10.1002/pol.1963.100010809
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectra and assignments for polyvinyl chloride and deuterated analogs

Abstract: SynopsisDeuterated analogs of polyvinyl chloride (PVC) have been prepared and their infrared spectra analyzed as an aid to the more detailed assignment of bands in the spectrum of PVC. The following deuterated polymcrs were studied: PVC-adl, PVC-fldl, PVC-mod2, and PVCd,. These, as well as PVC, were polymerized in urea-complex, at -78"C., and a t +50°C. in order to determine which bands are of crystalline origin and whi-h of noncrystalline origin. Polarized spectra of oriented samples were obtained in each cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0

Year Published

1971
1971
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 18 publications
4
56
0
Order By: Relevance
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 21 Inset picture in (b) shows the corresponding color change after reaction. Peak assignments obtained from ref [ 48 ], while vibration descriptors are consistent with the notation given in ref [ 47 ].…”
Section: Resultsmentioning
confidence: 96%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 21 Inset picture in (b) shows the corresponding color change after reaction. Peak assignments obtained from ref [ 48 ], while vibration descriptors are consistent with the notation given in ref [ 47 ].…”
Section: Resultsmentioning
confidence: 96%
“…[5][6][7][8] reveals a rather complicated behavior of the benzenethiolate 750 cm-' and 690 cm-' bands. The relationships are not linear in either solvent.…”
Section: Resultsmentioning
confidence: 96%
“…Some researchers [34][35][36] have shown that the C-Cl stretching bands of PVC, which normally occur at α (690 cmˉ1), β (638 cmˉ1), γ (615 cmˉ1) and δ (603 cmˉ1), are sensitive to crystallinity, stereo regularity, and configuration of the polymer chain. These end-group vibrations of the polymer segment are sensitive to the interaction of the other constituents of the complex.…”
Section: Ftir Analysismentioning
confidence: 99%